Interleukin-4 Enhances the Production of Anti-Inflammatory Macrophages That Inhibits the Growth of Osteoclasts to Improve Knee Functionality - Yousif, Haider; Alzamily, Ajil; Alsalman, Ihsan (Journal of Biomedicine and Biochemistry, 2022)
Background : The knee is one of the largest and most complicated joints in the body. Knee osteoarthritis is a common disease for many people in many countries, especially those who have an unbalanced and unhealthy lifestyle, where they suffer from pain and difficulty in movement. Given that treatments and medicines generally have side effects, it was possible to search for an alter- native treatment that is safer and it has the greatest effect. Platelet-rich plasma therapy is an important and useful treatment by injecting it locally into the knee joint, which allows for repairing the damage in the joint and rebuilding it at the level of the microenvironment. Significant disappearance of symptoms the in- nate immune system stimulates interleukin-4, an anti-inflammatory cytokine secreted by the body in response to the inflammation that occurs in the affected area of the body, where it works to stimulate the repair of damage. Patients and procedure This non-randomized controlled pilot study in- cluded 32 patients (18 females and 14 males) with knee osteoarthritis and 16 healthy subjects (5 females and 11 male) from November 2021 to June 2022. All KOA patients diagnosed by orthopedic specialists were based on clinical treat- ment and radiological findings (X-rays). They were divided into two groups based on the type of PRP; they received: 21 patients received a single injection of pure-PRP in the knee joint and 11 patients received a single injection of LR- PRP in the knee joint. The PRP were received by patients was 4 ml in the case of both groups. The ages of the participants (patients and control group) ranged between 35-75 years old. Outcomes were measured at two points at baseline and six months after injection with IL-4 as an indicator. Results The results of this study were showed that the concentration of IL-4 was significantly higher in KOA patients as compared to control subjects, and both the pure-PRP injected group and the LR-PRP injected group showed a significant decrease in the concentration of IL-4 after six weeks of intervention, but the pure-PRP injected group showed a higher reduction in the serum level of IL-4 as compared to the LR-PRP injected group. Conclusions In conclusion, pure-PRP and LR-PRP showed benefits in terms of inflammation reduction. In both groups, there was a significant reduction in the concentration of IL-4, but the pure-PRP gave a superior outcome as com- pared to the LR-PRP.